Challenges Faced In Covid Labor Room In First Wave In A Tertiary Care Centre-An Observational Study - Parneet Kaur; Satinder Pal Kaur; Divyanee Gulati (GMC Patiala Journal of Research and Medical Education, 2020)
Introduction: Coronavirus disease (COVID-19) is an infectious disease caused by Novel Corona Virus named SARS-CoV-2.TheWHO declared SARS-CoV-2 causing COVID-19, a pandemic on 11th March 2020.As pregnant women are particularly vulnerable to infectious diseases that can cause both maternal and foetal adverse outcomes, compared to their non-pregnant counterpart, it is important to know the impact of disease on mother as well as foetus. Aims & Objectives: To determine clinical manifestation risk factors and maternal and perinatal outcome in pregnant women with COVID-19 positive status. Material & Methods: A prospective observational study to render the challenges faced by our department during preparation for COVID LR facility and maternal and foetal outcome in COVID-19 positive patients. Also, to study changes made in infrastructure and working of department for obstetrical admissions since the beginning of COVID LR from 20th March 2020.Results: Total COVID-19 positive obstetrical admissions till 31/10/2020 were 175, out of which 104 (59.43%) patients delivered. LSCS was done in 54 (51.92%) Vaginal deliveries in 50(48.08%). 61(34.86%) patients were managed in antenatal period and 10(5.71%) were admitted as post-partum cases. Conclusion: It has been a successful journey with the efforts of whole isolation team in management of all COVID-19 pregnant patient by our dedicated healthcare workers.All the obstetrics complications were managed as per guidelines with use of proper personal protective equipment.